Real-time kinetic binding studies at attomolar concentrations in solution phase using a single-stage opto-biosensing platform based upon infrared surface plasmons - Allsop, Thomas P.; Mou, Chengbo; Neal, Ron M.; Mariani, Stefano; Nagel, David Andrew; Tombelli, Sara; Poole, Andrew J.; Kalli, Kyriacos; Hine, Anna V.; Webb, David J.; Culverhouse, Phil; Minunni, Maria; et al. (My University, 2017)
Here we present a new generic opto-bio-sensing platform combining immobilised aptamers on an infrared plasmonic sensing device generated by nano-structured thin film that demonstrates amongst the highest index spectral sensitivities of any optical fibre sensor yielding on average 3.4 × 104 nm/RIU in the aqueous index regime (with a figure of merit of 330) This offers a single stage, solution phase, atto-molar detection capability, whilst delivering real-time data for kinetic studies in water-based chemistry. The sensing platform is based upon optical fibre and has the potential to be multiplexed and used in remote sensing applications. As an example of the highly versatile capabilities of aptamer based detection using our platform, purified thrombin is detected down to 50 attomolar concentration using a volume of 1mm3 of solution without the use of any form of enhancement technique. Moreover, the device can detect nanomolar levels of thrombin in a flow cell, in the presence of 4.5% w/v albumin solution. These results are important, covering all concentrations in the human thrombin generation curve, including the problematic initial phase. Finally, selectivity is confirmed using complementary and non-complementary DNA sequences that yield performances similar to those obtained with thrombin.
Keywords: Surface plasmon resonance; Plasmons; SPR biosensor